The Species Composition and Relative Abundance of Insect Pests of Stored Faba Bean in Farta District of South Gondar Zone of North Western Ethiopia - Wondale Endshaw ,; Berhanu Hiruy, (Journal of Basic & Applied Sciences, 2020)
Faba bean contributes to meet the basic dietary needs of millions of people and animals around the world, including Ethiopia, pertaining to its high protein, carbohydrate, dietary fibers and micronutrients. Nevertheless, insect pests have been reported to cause significant loss of it under traditional farmers’ storages. Accordingly, survey involving sampling of stored faba bean from a total of 162 farmers stores selected in nested design was conducted from 4, September 2019 – 15, May 2020 in six major faba bean producing peasant associations of Farta District. Accordingly, a total of 10 species of insect pests viz Acanthoscelides obtectus, Callosobruchus sp., Callosobruchus chinensis, Zabrotes subfasciatus, Callosobruchus muculutus, Bruchus sp. and Bruchidius sp. were recorded from stored faba bean of the study area. 90% of which was belonging to order Coleoptera with in two families i.e., Bruchidae and Nitidulidae, while one species (10%) was from order Psocoptera of the family Liposcelididae. In terms of their relative abundance the species were in the following order Acanthoscelides obtectus > Callosobruchus sp. > Callosobruchus chinensis > Zabrotes subfasciatus > Callosobruchus muculutus > Carpophilus sp. > C. dimidatus > Liposcelis sp. > Bruchus sp. > Bruchidius sp. Accordingly, the presence of great infestation of the faba bean grain by pests was suggested. As a result, the traditional practices used by farmers were ineffective for satisfactory protection of the stored faba bean grains. Therefore, designing effective management strategies against insect pests of stored faba bean in the study area is urgently needed.